Three women in traditional Japanese clothing standing with young girl in Japanese Village, Alaska Yukon Pacific Exposition, Seattle, 1909 - Unidentified (1909)
PH Coll 792.PSJ1 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number